Tooth resorption—Part 2: A clinical classification. Issue 4 (23rd May 2022) - Abbott, Paul V.; Lin, Shaul
Abstract: Tooth resorption is either a physiological or a pathological process resulting in loss of dentin and/or cementum. It may also be associated with bone loss. Currently there is no universal classification for the different types of tooth resorption. This lack of a universal classification leads to both confusion amongst practitioners and poor understanding of the resorptive processes occurring in teeth which can result in incorrect/inappropriate diagnoses and mis‐management. When developing a classification of diseases and/or conditions that occur within the body, several criteria should be followed to ensure a useful classification. The classification should not only include pathological conditions but also physiological conditions. Since tooth resorption can be either pathological or physiological, a classification of tooth resorption should include both of these categories. Any classification of diseases should be possible to use clinically, meaningful, useful, clear and universal. It should enable easy storage, retrieval and analysis of health information for evidenced‐based decision‐making. It should also be possible to share and compare data and information between different institutions, settings and countries. A classification of tooth resorption should be developed by combining anatomical, physiological and pathological approaches. For some types of resorption, the aetiological approach should also be incorporated. A classification of tooth resorption that uses simple, relevant and appropriate terminology based on the nature and location of the resorptive process occurring in teeth is proposed. There are two broad categories of internal and external tooth resorption which are sub‐divided into three types of internal tooth resorption (surface, inflammatory, replacement) and eight types of external tooth resorption (surface, inflammatory, replacement, invasive, pressure, orthodontic, physiological, idiopathic). The clinician's understanding, diagnosis and management of tooth resorption can be facilitated by using this simple classification which should ideally be used universally by the entire dental profession to ensure clarity and to avoid confusion.